Smart traffic control system using ATMEGA328 micro controller and arduino software - Vahedha; Jyothi, B. Naga (2016 International Conference on Signal Processing, Communication, Power and Embedded System (SCOPES), 2016)
The work aims in designing an intelligent traffic controlling system. Traffic increases in proportion with the population especially in a developing country like India. Hence there is a great requirement to have well coordination of the traffic signals for the smooth control of traffic especially in busy traffic hours. The proposed work is developed so as to reduce traffic jams particularly when emergency vehicles are approaching towards the traffic junction. A Radio Frequency Identification Tag is provided to each vehicle which is highly intact. As the emergency vehicle approaches the traffic junction, RFID reader studies the signal conditions, a green wave is indicated and hence the vehicle passes smoothly without getting stuck in jam. As the vehicle crosses the traffic signal point automatic change is observed in the signals. Work is implemented keeping in view a multi road traffic junction point. The proposed work includes the following three applications. 1. Automatic vehicular signal control. 2. Detection of stolen vehicle. 3. Clearance to emergency vehicle/fire car.